Parathyroid Paranoia: Unveiling Psychosis in Hyperparathyroidism - Rachael J. Murphy; Subin Paul; Ralph Primelo (Case Reports in Psychiatry)
Primary hyperparathyroidism (PHPT) and subsequent hypercalcemia have been reported to be associated with psychosis. Here we report the case of a 28-year-old cannabis using male with his first contact with psychiatric care because of mood instability, bizarre behavior, and poor ability to carry out activities of daily living. Hypercalcemia was identified, and a subsequent endocrine workup confirmed PHPT. After parathyroidectomy, there was no longer any need for antipsychotic or other psychotropic medications; the report emphasizes the importance of considering organic causes, such as hyperparathyroidism, in patients presenting with psychotic-like symptoms, including in the setting of substance use disorder. Prompt recognition and appropriate management of the underlying condition are crucial for optimizing patient outcomes.